HOW THE KONDO EFFECT CAN EXIST IN Gd INTERMETALLIC COMPOUNDS (Journal of Sciences, Islamic Republic of Iran)
Based on the crystal and magnetic structural properties of some Gd intermetallic compounds, it is shown that with increasing conduction electron concentration, Gd experiences electronic and magnetic instability, and that these behaviors point to the appearance of Kondo Lattice. We suggest that the conduction electrons have gained local character. It is shown that Kondo effect should be observed at around x=0.4. Resistivity studies confirm the calculations, and a Kondo temperature of around 70 K found for Gd2Au0.4Al0.6.